2021
DOI: 10.4081/ejtm.2021.10006
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of aquatic physical exercise programs on functional fitness in older adults

Abstract: The practice of physical exercise is recommended in the prevention of the deterioration of neuromuscular functions in aging. The objectives of this systematic review were to describe the protocols used and the functional fitness indicators evaluated in aquatic exercise programs in adults aged 50 to 80 years. The Pubmed database was used. The keywords were: 1) Physical exercise program or protocols or duration or type of exercise or aquatic exercise, frequency or intensity or indicators; 2) Adults or older adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…For instance, the systematic review by Bergamin et al [16] that analyzed the effectiveness of water-based exercise interventions in older adults reported strong evidence underpinning the use of this type of exercise to promote cardiorespiratory fitness and muscle strength. Similar conclusions were reported in a more recent systematic review [37] that underlined the positive responses on functional fitness after participating in WBE programs in healthy older adults. In this case, specific recommendations regarding the training characteristics (i.e., frequency, duration, intensity) were also provided.…”
Section: Discussionsupporting
confidence: 88%
“…For instance, the systematic review by Bergamin et al [16] that analyzed the effectiveness of water-based exercise interventions in older adults reported strong evidence underpinning the use of this type of exercise to promote cardiorespiratory fitness and muscle strength. Similar conclusions were reported in a more recent systematic review [37] that underlined the positive responses on functional fitness after participating in WBE programs in healthy older adults. In this case, specific recommendations regarding the training characteristics (i.e., frequency, duration, intensity) were also provided.…”
Section: Discussionsupporting
confidence: 88%
“…It is also congruent with the systematic review by (Song & Oh, 2022), which confirmed that the exercise programs are effective and safe for patients with knee OA. A comparison of the effectiveness of aquatic and land-based exercises favoured aquatic exercises as more satisfactory for patients with knee OA (Dong et al, 2018) .Aquatic exercises had also been found to improve functional capacity and fitness when administered in older adults (Lopez et al, 2021). The properties of water like waves, water temperature, and hydrostatic pressure provide relaxation of muscles and soothing effects to the joints to help alleviate pressure from joints and reduce the pain caused by compression on the joint (Bender et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Lifestyle modification, particularly regular exercise, is recommended as a nonpharmacological therapeutic strategy for managing T2DM (Leite et al, 2020). The underlying principle is that working muscles enhance insulin sensitivity and promote glucose metabolism (Mogharnasi et al, 2019), positively affecting glycemic control, body composition, endothelial function, physical fitness, functional capacity, and self-reported wellbeing (Balaji et al, 2011;Barrows & Fleury, 2022;Fuentes-Lopez et al, 2021;Honda et al, 2021).…”
Section: Introductionmentioning
confidence: 99%